Underreporting of Workplace Violence: Comparison of Self-Report and Actual Documentation of Hospital Incidents. (May 2015) - Arnetz, Judith E.; Hamblin, Lydia; Ager, Joel; Luborsky, Mark; Upfal, Mark J.; Russell, Jim; Essenmacher, Lynnette
This study examined differences between self-report and actual documentation of workplace violence (WPV) incidents in a cohort of health care workers. The study was conducted in an American hospital system with a central electronic database for reporting WPV events. In 2013, employees ( n = 2010) were surveyed by mail about their experience of WPV in the previous year. Survey responses were compared with actual events entered into the electronic system. Of questionnaire respondents who self-reported a violent event in the past year, 88% had not documented an incident in the electronic system. However, more than 45% had reported violence informally, for example, to their supervisors. The researchers found that if employees were injured or lost time from work, they were more likely to formally report a violent event. Understanding the magnitude of underreporting and characteristics of health care workers who are less likely to report may assist hospitals in determining where to focus violence education and prevention efforts.